The Effectiveness Of Civil Servant Training In Improving The Performance Of Local Government Apparatus - Anace Kambu; Dian Ferriswara; Sarwani Sarwani; Sri Kamariyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the effectiveness of education and training programs in improving employee performance and identifies the factors influencing training outcomes at the Personnel and Human Resources Development Agency (BKPSDM) of Southwest Papua Province. A qualitative descriptive approach was employed, utilizing interviews, observations, and documentation, with key informants including the Head of BKPSDM. Data were analyzed using the interactive model of Miles et al. (2014), encompassing data condensation, data display, and conclusion drawing. Findings reveal that education and training programs at BKPSDM significantly enhanced employee performance, as evidenced by improved timeliness in task completion, increased knowledge, skills, and expertise, and notable positive changes in employee behavior and attitudes. Training outcomes were also reflected in improved workplace discipline and greater responsibility among civil servants. Evaluation of program effectiveness employed five levels: participant reaction, learning achievement, behavioral change, organizational impact, and cost-effectiveness, all of which indicated favorable results. Factors influencing training effectiveness included the relevance of training materials to employee roles, appropriate scheduling that minimized work disruption, the use of clear and supportive training methods, and the competence of instructors in delivering material effectively. These findings demonstrate that well-planned and well-delivered training programs can strengthen the capacity and professionalism of civil servants, enabling them to better fulfill governmental and developmental responsibilities while supporting overall organizational performance improvement. In addition, the study highlights the importance of continuous monitoring and feedback throughout the training process to ensure sustained improvements in employee performance. It suggests that the involvement of employees in the design and planning stages of training programs can enhance the relevance and applicability of the content, fostering greater engagement and retention of knowledge.